Experimental enlargement of nest size does not increase risk of predation or brood parasitism in the Great Reed Warbler Acrocephalus arundinaceus. (6th March 2015) - Jelínek, Václav; Procházka, Petr; Honza, Marcel
Abstract : We assessed whether nest size affects the probability of nest loss using dyads of large and small (large being twice the size of small) inactive Great Reed Warbler Acrocephalus arundinaceus nests placed at similar sites in Great Reed Warbler territories. Large nests were not predated significantly more frequently than small nests. Experimentally enlarged active Great Reed Warbler nests suffered non‐significantly higher predation compared with non‐manipulated control nests. Our experiments did not support the nest‐size hypothesis and suggested that nest size does not appear to be a factor affecting the risk of nest predation in this species. The probability of brood parasitism by the Common Cuckoo Cuculus canorus was also unaffected by experimental nest enlargement, supporting the commonly accepted hypothesis that the Common Cuckoo searches for suitable host nests by host activity during nest building rather than nest size.